2011
DOI: 10.1002/ejoc.201001554
|View full text |Cite
|
Sign up to set email alerts
|

Gaining Control: Direct Suzuki Arylation of Dihydroazulenes and Tuning of Photo‐ and Thermochromism

Abstract: A protocol for functionalizing the seven‐membered ring of the DHA/VHF photochromic system via a Suzuki cross‐coupling was developed. Kinetic studies reveal that direct attachment of an aromatic moiety on the seven‐membered ring strongly affects the thermal back reaction. By the introduction of an anilino group, pH control of both the photochromic and thermochromic properties was obtained. Furthermore, it was possible to switch between three different states: two photochromic and one thermochromic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 17 publications
3
45
0
Order By: Relevance
“…The effect on the transition-state of the VHF by the presence of SWNTs is in line with previous observations [18,19], where it was shown that the electronic nature of substituents on DHA/VHF system greatly affects the rate of the thermal back reaction. 3 Conclusions SWNTs were functionalized with orthogonal dipole switches taking advantage of the exclusively thermally back-isomerization process.…”
supporting
confidence: 86%
“…The effect on the transition-state of the VHF by the presence of SWNTs is in line with previous observations [18,19], where it was shown that the electronic nature of substituents on DHA/VHF system greatly affects the rate of the thermal back reaction. 3 Conclusions SWNTs were functionalized with orthogonal dipole switches taking advantage of the exclusively thermally back-isomerization process.…”
supporting
confidence: 86%
“…Future work will seek to investigate the influence of separating the two DHAs by other spacers and having more than two DHA units working in concert in related DHA oligomers. Further functionalization of the DHA dimers in the seven‐membered rings by our previously developed9a,b, 22 bromination–elimination cross‐coupling protocol might also allow further tuning of the switching properties.…”
Section: Resultsmentioning
confidence: 99%
“…Fine‐tuning of the rate of ring closure (VHF→DHA) has been accomplished by substitution with either electron‐withdrawing and/or ‐donating groups with kinetics behavior that satisfies Hammett correlations,9 and it has also been shown that having a strong electron acceptor such as a buckminsterfullerene (C 60 ) covalently attached to DHA quenches the light‐induced ring opening 10. Also, by reversible oxidation of a covalently attached ferrocene or tetrathiafulvalene unit,11 or by protonation of an aniline substituent9a,b the photochromism of the DHA/VHF couple can be controlled. Along this line, molecules with two photochromic units have attracted interest as multimode switches.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, both reactions proceeded through an isomerization by which the ruthenium–alkynyl substituent shifted from position 7 to position 6 on the DHA core. Partial 7/6‐isomerization has previously been observed as a result of a light–heat cycle (ring‐opening/ring‐closure), yielding mixtures of the two isomers . In the present case, however, the isomerization does not involve irradiation.…”
Section: Resultsmentioning
confidence: 68%